Analisa Strategi Pemasaran Ekspor Cv Amartha Indotama Dalam Memasuki Pasar Global - Fitriyani Fitriyani; Retno Widowati PA; Sutrisno Wibowo (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2015)
In this thesis, the authors examined about the export marketing strategy analysis CV Amartha Indotama in entering global markets. The purpose of this research is to study the export marketing strategies that have been implemented, identify external factors and internal factors within the company, as well as  formulate  export marketing alternative strategy  for the company in the future. The object of this research is an export company CV Amartha Indotama, while the subject of research is the entire staff of employees of the company, amounting to 12 people. Data were collected using method are observation, interviews, and questionnaires. Technical analysis of the data in this study using SWOT analysis, IFAS, EFAS, and internal-external matrix. Based on Internal External matrix, a position the company is in cell 1 is growt which concentrates on vertical integration, and alternative strategies that can be given is backward integration (take over the function of the supplier), and forward integration (taking over the function distrubutor).